Negotiating Between Identities: Indonesia’s Chinese-Language Newspapers in the Post-New Order Era - Yuhao Wen (Universitas Pelita Harapan, 2018)
This study aims to provide a description of Chinese-Indonesian identity in the post-New Order era. Under the previous authoritarian regime, public expression of Chinese identity in all social fields, such as culture, language and politics, was officially suppressed by the government through its assimilation policy. A person could be Chinese or Indonesian, but not both. Since the collapse of the New Order government in 1998, Indonesia has begun the process of democratization, and the old Indonesian identity and cultural heritage of Indonesia has been